2321. Long-term immunogenicity of Ad26.RSV.preF/RSV preF protein vaccine against RSV in a phase 2b study by age and risk level. (15th December 2022) - Comeaux, Christy A; Falsey, Ann R; Williams, Kristi; Bart, Stephan; Ervin, John E; Bastian, Arangassery R; Menten, Joris; De Paepe, Els; Vandenberghe, Sjouke; Chan, Eric K H; Sadoff, Jerald; Douoguih, Macaya; et al.
Abstract: Background: Respiratory syncytial virus (RSV) can cause serious lower respiratory tract disease (LRTD) among older adults. There is no licensed RSV vaccine. In CYPRESS (a randomized, double-blind, placebo-controlled, phase 2b proof-of concept trial; NCT03982199), an Ad26.RSV.preF/RSV preF protein vaccine demonstrated 80.0% efficacy for prevention of RSV LRTD and 69.8% efficacy for prevention of any RSV acute respiratory infection in adults aged ≥65 years through the first RSV season. This study evaluated the durability of immune responses elicited by Ad26.RSV.preF/RSV preF protein after two RSV seasons (up to 1.5 years post-vaccination) in the overall study population and in groups of participants stratified by age and risk level for severe RSV LRTD. Methods: Participants (N=5782) were randomized 1:1 to receive vaccine or placebo before the RSV season. The primary endpoint was first occurrence of RSV LRTD. RSV A2 virus neutralizing antibodies (VNAs; through Day 365), RSV preF binding antibodies (through Day 533), and RSV-F–specific IFN-γ enzyme-linked immune absorbent spot (ELISpot; through Day 533), were evaluated in an immunogenicity subset (n=195; ages 65–74 years: n=141; 75–84 years: n=47; ≥85 years: n=6; increased risk [chronic heart or lung disease]: n=48; non-increased risk: n=147). Results: In the vaccine group of the immunogenicity subset, RSV A2 VNAs peaked at Day 15 and were maintained at 2.8-fold over baseline at 1 year. Similarly, RSV preF-specific binding antibodies peaked at Day 15 and were maintained at 2.1-fold above baseline at 1.5 years. Median RSV-F–specific IFN-γ T-cell frequency increased from 34 spot-forming cells (SFC)/10 6 peripheral blood mononuclear cells (PBMCs) at baseline to 143 SFC/10 6 PBMCs at 1.5 years. Comparable immune responses were observed in age/risk subgroups. No relevant changes were observed in the placebo group at any time point. Pre-existing Ad26 VNAs did not appear to impact RSV-specific immune response durability. Conclusion: Ad26.RSV.preF/RSV preF protein vaccine was efficacious and elicited robust, durable (to at least 1.5 years) humoral and cellular immune responses in adults aged ≥65 years, older participants (≥75 years), and in participants with increased risk for severe RSV LRTD. Disclosures: Christy A. Comeaux, MD, PhD, Janssen Vaccines & Prevention B.V.: Employee Ann R. Falsey, MD, BioFire Diagnostics: Grant/Research Support|Janssen: Grant/Research Support|Merck Sharp & Dohme: Grant/Research Support|Novavax: Advisor/Consultant|Pfizer: Grant/Research Support Kristi Williams, PhD, Janssen Research and Development: Employee John E. Ervin, MD, The Alliance for Multispecialty Research – KCM: Contractual agreement for conduct of study protocol Arangassery R. Bastian, PhD, Janssen Vaccines & Prevention BV: Employee Joris Menten, PhD, Janssen Infectious Diseases: Employee Els De Paepe, MSc, Janssen Infectious Diseases: employee Sjouke Vandenberghe, PhD, Janssen Infectious Diseases: Employee Eric K. H. Chan, PhD, Janssen Global Services, LLC: Employee Jerald Sadoff, MD, Janssen Vaccines & Prevention BV: Employee Macaya Douoguih, MD, MPH, Janssen Vaccines & Prevention B.V.: Employee Benoit Callendret, PhD, Janssen Vaccines & Prevention B.V.: Employee Esther Heijnen, MD, PhD, Janssen Vaccines & Prevention B.V.: Employee.